The present situation of Japanese company’s purpose: It focuses on the relation with business creed - Haruhiko NOBAYASHI (AAOS Transactions)
It did the investigation about the present situation of Japanese company’s “ Purpose” establishment. An investigation object is 91 companies carried on “PURPOSE STATEMENT LIST 2022” that SMO Inc. created. That name has “purpose” and much “importance of existence” that are that equivalent term in translation, but there is “the will”, too. The corporation that establishes “Purpose” increases rapidly from 2020. The company’s CEO often establishes and makes public a purpose within 2 years of the installation. It is often established made public with a medium-term business planning and long-term vision. And corporate purpose is often established in the influence of SDGs and ESG management. In the relation with an existing business creed, there is the one made as the case combined, additional, and completely new one, too.